Feasibility Analysis of Sheep Slaughterhouse Business Investment in Geraldton Australia Using Monte Carlo Simulation - Setiawan, Devi Avianto; Purnomo, Hadi; Wahyuningsih, Sri (Universitas Ibn Khladun Bogor, 2024)
This study was conducted to examine the investment feasibility of a sheep abattoir business in Geraldton, Australia, using traditional methods and Monte Carlo simulation. The study is distinguished by the integration of two different investment analysis approaches, which addresses a gap in the existing literature regarding the assessment of investment feasibility in the agribusiness sector through the application of Monte Carlo simulation. Using a quantitative approach, this study employs Net Present Value (NPV) and Internal Rate of Return (IRR) analysis to evaluate investment feasibility. Information was collected from various sources and processed using Microsoft Excel to conduct 10,000 iterations of Monte Carlo simulation. The theoretical framework of this study includes company valuation theory and Monte Carlo simulation. The findings show that Monte Carlo simulation offers a more in-depth understanding of the risks and potential returns associated with an investment compared to traditional methods. The assessment of the probability of profitability through Monte Carlo simulation shows favorable results, thus confirming the feasibility of this investment. Therefore, NPV and Monte Carlo simulation emerge as powerful instruments for evaluating investments in the agribusiness sector.